English Legal System - Cracknell (Old Bailey Press, 2004)
Although the english legal system has its roots in a distant past, a large part of it is now governed by modern statues. Many significant changes were made by the Courts and Legal Services Act 1990 and the Acces to Justice Act 1999 gave effect to a wide-ranging programme of reform concerning the courts, legal aid and the provision of legal service.